2023
DOI: 10.1371/journal.pone.0292402
|View full text |Cite
|
Sign up to set email alerts
|

ACE I/D genotype associates with strength in sarcopenic men but not with response to ACE inhibitor therapy in older adults with sarcopenia: Results from the LACE trial

Christos Rossios,
Tufail Bashir,
Marcus Achison
et al.

Abstract: Background Angiotensin II (AII), has been suggested to promote muscle loss. Reducing AII synthesis, by inhibiting angiotensin converting enzyme (ACE) activity has been proposed as a method to inhibit muscle loss. The LACE clinical trial was designed to determine whether ACE inhibition would reduce further muscle loss in individuals with sarcopenia but suffered from low recruitment and returned a negative result. Polymorphic variation in the ACE promoter (I/D alleles) has been associated with differences in ACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…We performed a post hoc subgroup analysis between perindopril and no perindopril groups to test if the medication may have affected this outcome and found that this persisted in the no perindopril group, but was negated by the presence of perindopril. This is a similar finding to that seen in our recent study of ACE gene variants, where perindopril negated the improvement in SPPB score seen among ID/II genotypes who were not taking perindopril [ 9 ]. The findings in the both studies may be explained by the effect of being recruited into a trial leading to increased activity and physical improvement–those taking perindopril suffered a higher rate of adverse events and poorer quality of life as reported in the trial [ 16 ], which may have reduced their motivation to remain active, and this could be most capitalised among +9+9 genotypes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We performed a post hoc subgroup analysis between perindopril and no perindopril groups to test if the medication may have affected this outcome and found that this persisted in the no perindopril group, but was negated by the presence of perindopril. This is a similar finding to that seen in our recent study of ACE gene variants, where perindopril negated the improvement in SPPB score seen among ID/II genotypes who were not taking perindopril [ 9 ]. The findings in the both studies may be explained by the effect of being recruited into a trial leading to increased activity and physical improvement–those taking perindopril suffered a higher rate of adverse events and poorer quality of life as reported in the trial [ 16 ], which may have reduced their motivation to remain active, and this could be most capitalised among +9+9 genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…The ACE I allele has been associated with a higher proportion of type I muscle fibres which may explain its link with enhanced endurance performance [ 8 ]. We have also recently shown that the I allele is under-represented in sarcopenic men and that sarcopenic men with the I allele had higher leg strength than DD individuals suggesting a role for the RAS in sarcopenia, at least in men [ 9 ].…”
Section: Introductionmentioning
confidence: 99%